Nigeria’s Economic Development Process and the Challenges of Corruption - Eneasato, Benjamin; Mbaeze, Netchy Christian (ESUT JOURNAL OF SOCIAL SCIENCES, 2019)
There is a discernible wide expectation gap in the way governments of Third World countries manage their nation’s resources over time; the intensive, extensive and sustainable propaganda of democratic dividends notwithstanding. The citizens of Third World countries want to see the dividends of democracy, for all and sundry, through improved living conditions commensurate to the volume, value and varieties of their national resources. This is the citizens’ constitutional right. But effectual results from prudent management of nations’ resources as expected from governments to justify their mandates are far from been realized. This study, Third World economies and the need for global collaboration on the war against corruption is qualitative in nature. Data is basically drawn from secondary sources while recourse is taking to content analysis in doing justice to the data extracted from relevant and extant literature. This paper established that corruption in Third World countries is multifaceted and has tremendous socio-economic and political implications. Corruption indeed is a global phenomenon and thus calls for global collaboration in dealing with it. The paper pays particular attention on capital flight and money laundering as derivatives of corruption that affects Third World economies on a global scale and interrogates how global collaboration may help Third World economies come out of the woods in the anti-corruption efforts using Nigeria as reference point.